SYSTEMATIC LITERATURE REVIEW: SELF-REGULATED LEARNING ON MATHEMATICAL PROBLEM-SOLVING ABILITY - Ainia Refi Mafaza; Indah Nur safira; Maulida Uswatin Khasanah; Dina Fakhriyana (Universitas Cokroaminoto Palopo, 2024)
The ability to solve problems is a crucial component that students must possess when learning mathematics. For students to develop these abilities, self-regulated learning is necessary. This study examines the impact of self-regulated learning on mathematical problem-solving abilities as well as abilities as indicators of mathematical problem-solving abilities that are affected by self-regulated learning. The method used in this research is the Systematic Literature Review (SLR) method, where researchers will review several related previous articles. In the data search, there were 347 articles from the period 2013–2023, which were then selected based on inclusion and exclusion criteria to obtain 25 articles that were suitable for study by researchers. The results of the research conducted include: (1) there is a significant positive influence of self-regulated learning on mathematical problem-solving abilities; (2) someone with self-regulated learning Highly capable of meeting 4 indicators of mathematical problem-solving ability according to Polya, someone with self-regulated learning being only able to meet 2 indicators of mathematical problem-solving ability according to Polya, and someone with self-regulated learning being low, only able to meet 1 indicator of mathematical problem-solving ability according to Polya or not even able to solve existing problems.